TEST OF AMYLASE INHIBITION ACTIVITY OF Melicope PLANTS WHICH POTENTIAL AS ANTIDIABETIC AGENTS - Nurjanah, Siti; Marliana, Eva; Astuti, Winni (JURNAL ATOMIK, 2020)
The test of amylase inhibition activity of the leaves of Melicope lunu-ankenda and bark of Melicope glabra (BI.) T.G. Hartley extracts were done. The objective of this study was to determine in-vitro Î±-amylase inhibition activity against two samples by DNS method. The result showed that two samples of Melicope lunu-ankenda leaves and bark of Melicope glabra (BI.) TG Hartley displayed the enzyme inhibitory effect with percent inhibitions of 48.71% and 46.36%. Two sample extracts can inhibit amylase. It can be suggested that about sample were potential as antidiabetic agents.